Fine-needle aspiration biopsies of thyroid nodules - Cordes, Michael; Schmidkonz, Christian; Horstrup, Karen; Weppler, Matthias; Kuwert, Torsten (Nuklearmedizin-Nuclear Medicine, 2018)
OBJECTIVE: The purpose of the study was the characterization of adverse events (AEs) after fine-needle aspiration biopsies (FNABs) of thyroid nodules, as well as possible predisposing factors. METHODS: A total of 205 patients, each of whom had undergone an FNAB of a thyroid nodule, were included in the study (15 of whom were taking anticoagulant medication). The thyroid nodules were classified according to the ultrasound criteria of the American Thyroid Association (ATA). The FNABs were carried out by four trained nuclear medicine specialists from two institutions. To detect AEs, all patients were asked to fill out a standardized self-assessment questionnaire. RESULTS: Out of 205 patients, 189 (92 %) reported no AEs. Fourteen patients (6.8 %) had mild or moderate AEs, such as short-term pain at the puncture site. In two patients (1 %), the AEs were classified as significant, and required medical followup, which revealed an intrathyroid hematoma in one patient and dysphonia in the other. All AEs were reversible. None of the patients taking anticoagulants experienced any AEs. The parameters of age, sex, nodule volume, ATA nodule type, needle size, and physician performing the biopsy were not predisposing factors for side effects (p = 0.54, p = 0.73, p = 0.75, p = 0.94, p = 0.35, and p = 0.24, respectively). CONCLUSIONS: The vast majority of patients tolerated the FNAB very well. AEs were seldom observed. A small number of patients experienced AEs that required no intervention or could be self-managed by the patient. Considering the almost negligible risk of the procedure, FNAB should be increasingly used for the classification of thyroid nodules. ZIEL:: Das Ziel der Studie war die Erfassung unerwünschter Wirkungen (UWs) nach Feinnadelaspirationsbiopsien (FNABs) von Schilddrüsenknoten und mögliche hierfür prädisponierende Faktoren. METHODIK: 205 Patienten, bei denen eine FNAB wegen eines Schilddrüsenknotens erfolgte, wurden in die Studie eingeschlossen (hiervon 15 Patienten mit gerinnungshemmender Medikation). Die Schilddrüsenknoten, wurden gemäß Ultraschallkriterien der American Thyroid Association (ATA) klassifiziert. Die FNABs erfolgten durch vier trainierte Nuklearmediziner aus zwei Institutionen. Für die Erfassung von UWs erhielten alle Patienten einen standardisierten Selbstbeurteilungsfragebogen. ERGEBNISSE: Von 205 Patienten gaben 189 (92 %) keine UWs an. 14 Patienten (6,8 %) hatten geringe oder moderate UWs - wie Schmerzen an der Punktionsstelle von kurzer Dauer. Bei zwei Patienten (1 %) wurden die UWs als relevant klassifiziert und erforderten eine ärztliche Nachuntersuchung. Dabei wurde ein intrathyreoidales Hämatom bzw. eine Dysphonie diagnostiziert. Alle UWs waren reversibel. Bei keinem Patienten, der Antikoagulanzien erhielt, fand sich eine UW. Die Parameter Alter, Geschlecht, Knotenvolumen, ATA Knotentyp, Punktionsnadelstärke sowie durchführender Arzt waren für UWs keine prädisponierenden Faktoren (jeweils mit p = 0,54, p = 0,73, p = 0,75, p = 0,94, p = 0,35, p = 0,24, resp.). SCHLUSSFOLGERUNG: Die große Mehrheit von Patienten toleriert die FNAB sehr gut. UWs wurden selten beobachtet. UWs, die bei einer kleinen Zahl von Patienten auftreten, bedürfen entweder keiner Intervention oder können durch die Patienten selbst gemanagt werden. Aufgrund eines fast vernachlässigbaren Risikos sollte die FNAB zur Dignitätsabklärung von Schilddrüsenknoten verstärkt eingesetzt werden.
EVALuna2:212296